Towards an ethics framework for Australian health promotion practitioners: An exploratory mixed methods study. (23rd March 2021) - Blackford, Krysten; Leavy, Justine; Taylor, Jane; Connor, Elizabeth; Crawford, Gemma
Abstract: Issue addressed: Ethical values underpin the health promotion discipline and profession, and competencies required for professional practice. Understanding how ethical values are translated into professional practice is critical. The aim of this exploratory sequential mixed methods study was to explore Australian health promotion stakeholder perspectives about ethical health promotion practice. Methods: A face‐to‐face group‐based workshop (n = 15), online survey (n = 77) and in‐depth individual interviews (n = 15) collected qualitative and quantitative data from health promotion stakeholders. Descriptive statistics were used to analyse quantitative and thematic analysis to analyse qualitative data. Results: Tensions emerged regarding the nomenclature of ethical health promotion practice, with ethics framed largely by participants as related to formal approval for research. A range of barriers and enablers to ethical practice were identified. Barriers related to obtaining ethical approvals and working with specific population groups and communities. Enablers included professional development opportunities, access to a specialised human research ethics committee and a better understanding of what is meant by 'ethical practice'. Conclusion: Findings suggest the need for an ethical health promotion practice framework and resources for practitioners and organisations throughout Australia. We propose a framework comprising two pillars: (a) developing critical practice; and (b) building the evidence‐based for health promotion. So what?: This study recognises the need for increased dialogue about the ethical foundations of health promotion. The development of a health promotion ethics framework can better support the development of ethical practice in the Australian health promotion discipline and profession.